2021
DOI: 10.1016/j.mbplus.2021.100078
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of elastic fibre and microfibrillar proteins

Abstract: Elastic tissues owe their functional properties to the composition of their extracellular matrices, particularly the range of extracellular, multidomain extensible elastic fibre and microfibrillar proteins. These proteins include elastin, fibrillin, latent TGFβ binding proteins (LTBPs) and collagens, where their biophysical and biochemical properties not only give the matrix structural integrity, but also play a vital role in the mechanisms that underlie tissue homeostasis. Thus far structural information rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 148 publications
(185 reference statements)
0
4
0
Order By: Relevance
“…FBN1 is the main component of elastic fiber assembly scaffold microfiber, and it is the basis for the final formation of fiber bundle shape of elastic fiber. Knockdown of FBN1 in mice, the elastic fibers showed fragmentation, accompanied by arterial bending and active phenotypic defects such as aneurysm (Singh et al, 2021). It is suggested that CDH11 increases the expression of ELN, LOX and FBN1, to promote the formation of reticular cross-linked collagen and elastic fiber bundles and increase the mechanical properties of the engineered cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…FBN1 is the main component of elastic fiber assembly scaffold microfiber, and it is the basis for the final formation of fiber bundle shape of elastic fiber. Knockdown of FBN1 in mice, the elastic fibers showed fragmentation, accompanied by arterial bending and active phenotypic defects such as aneurysm (Singh et al, 2021). It is suggested that CDH11 increases the expression of ELN, LOX and FBN1, to promote the formation of reticular cross-linked collagen and elastic fiber bundles and increase the mechanical properties of the engineered cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrillin is the major component of microfibrils. There are species- and tissue-dependent differences in the expression levels of three isotypes of fibrillin, with fibrillin-1 being the predominant isotype found in adult human tissues [ 9 , 88 , 89 , 90 ]. Although fibrillin is the major component of the microfibrils, an array of other less abundant molecules is necessary, including latent transforming growth factor-β binding proteins (LTBPs), matrix-associated glycoproteins (MAGPs), members of the fibulin family, and PGs.…”
Section: Elasticity Of Soft Tissuesmentioning
confidence: 99%
“…They play an essential role in the organization of fibers, but also their complex hierarchical assembly supports the biological functions of microfibrils, including induction of cellular responses to mechanical forces derived from the matrix microenvironment [ 10 , 14 , 87 , 91 ]. Therefore, the two basic components of an elastic fiber have distinct tasks in the tissue ECM; elastin stores energy of deformation and provides passive recoil, whilst fibrillin microfibrils direct elastogenesis, mediate cell signaling, and maintain tissue homeostasis [ 9 , 11 , 14 , 89 , 90 ].…”
Section: Elasticity Of Soft Tissuesmentioning
confidence: 99%
“…In mature tissues, elastic fibres are formed by a central component, elastin, surrounded by a mantle of microfibrils, mostly composed of fibrillin-1 and other glycoproteins (Singh et al, 2021). While microfibrils appear to act as a protective scaffold, the central elastin core, which represents about 90% of the fibre, is responsible for resilience as well as elastic recoil.…”
Section: Introductionmentioning
confidence: 99%